Assessment of Climate Driven Changes in Flow Series of Alpine Basin: A Case Study of Danube River Basin - Laghari, A. N.; Rajper, A.; Walasai, G. D.; Jatoi, A. R.; Jalbani, N. B.; Soomro, H. (Engineering, Technology & Applied Science Research, 2018)
This study was carried out in order to analyze the climate change driven influence on mean monthly flow series of Danube River and its tributaries during the last century. The study confirms some signs of climate driven alterations in monthly river flow series along with change in flow seasonality during the last century. In spite of this, man-made interference in the basin like i.e. groundwater extraction, irrigation, river regulation, land use alteration and urbanization, has significantly changed Danube flow regime in most areas of the catchment. The analysis of Achleiten station demonstrates that average annual flow regime is a little bit increased. Major increase is observed in winter and autumn months and decrease in summer months. These seasonal alterations clearly signal a future glimpse of reduced water availability in alpine basins. This will mainly occur due to the change in the form of precipitation in winter, from snow to rain and the consequent less snow accumulation, and the early melt of snow storage, less precipitation and high evaporation rate in summer.